The Effect of Zig-Zag Running Games on Gross Motor Skills of Early Childhood Group B at Paud IT Auladuna 1 Bengkulu City - Amanda Amelia Imel; Delrefi; Septi Fitriana (Journal of Early Childhood Development and Education, 2024)
Finding out how zigzag running games affect young children's gross motor abilities is the goal of this study. Researchers employed quantitative research, or pseudo-experimental methodology. The youngsters in group B at PAUD IT Auladuna 1 Bengkulu City comprised the study population. Using random sampling, 36 children from classes B2 and B5 made up the research sample. There was testing done on the data gathering method. This data analysis method applied the t test. As expected, during the teaching and learning process, the control class learning with body exercise center games had an average value of 70.00, but the zig-zag running game had an average value of 85.56.At a significance level of 0.05, the hypothesis test results indicate that tcount> ttable is 3.909> 1.691. This indicates that, in comparison to the control class, the experimental class receiving the treatment experiences a notable change in value. The findings indicate that group B early childhood students at PAUD IT Auladuna 1 Bengkulu City had improved gross motor abilities as a result of playing zigzag running games. It is recommended that (1) educators utilize it as a substitute for instruction to help early childhood students' gross motor abilities grow and (2) future researchers use it as an inspiration to conduct research and play other games to help kids improve their gross motor skills.